AKTIVITAS PROTEASE DAN AMILASE PADA IKAN SIDAT Anguilla bicolor McClelland) - Mohamad Taufik; Hana Hana; Untung Susilo (Fakultas Biologi | Universitas Jenderal Soedirman, 2017)
This study was experimental, conducted using a Completely Randomized Design (CRD) with 3 x 2 factorial design, and four replicates have been carried out to evaluate the protease and amylase activities of Anguilla bicolor McClelland. A total of 71 individuals divided into three weight groups were used in this study. The first group with an average weight of 41.25 ± 0.898 g consisted of 51 eels, the second with an average weight of 319.8 ± 4.666 g composed of 14 eels, and the third with a mean weight of 569.5 ± 9.150 g consisted of 6 eels. The results showed the protease activity differed significantly based on eel size and intestinal segment (P ˂ 0.05). This research recorded the highest protease activity was in eels within the smallest weight group (41.25 ± 0.898 g). This study also revealed the protease activity in the anterior intestine was higher than the posterior in all size of eels. The amylase activity did not differ significantly (P>0.05) by eel size and intestinal segment. This study concluded the protein digestion capacity of smaller eels was higher than larger eels, and the protein digestion capacity was greater in the anterior intestine than the posterior intestine. The carbohydrate absorption capacity in eel was not affected by the variety of fish size which indicates no change in the feed category.